Strategi Komisi Independen Pemilihan Kabupaten Pidie dalam Meningkatkan Angka Partisipasi Pemilih Marginal pada Pemilu 2019 - Zulfan Zulfan; Muryanto Amin; Arifin Saleh (Universitas Medan Area, 2022)
This study aims to determine what steps aretaken by the Independent Election Commission (KIP) of Pidie Regency in increasing the level of marginal voter participation. And want to know what strategy the Independent Election Commission (KIP) of Pidie Regency has done in increasing the level of marginal voter participation. The research method used in this study is a qualitative research method with a descriptive approach. The theory used in this research is political participation theory, election theory and strategy theory. Where from the results of his research, it was obtained that the low level of marginal voter participation was caused by several factors, including (1) apathy, (2) lack of understanding and education on elections (3) candidates who were carried out were not in line with expectations (4) there was a promise politics that are not fulfilled (5) prioritize daily needs, (6) there is no change and improvement in every election implementation. Actors that can increase voter participation are community leaders, religious leaders or elders in the gampong area. And the strategy taken by the Independent Election Commission (KIP) of Pidie Regency in increasing the participation rate of marginal voters is to increase socialization activities to the maximum and massively by involving democratic volunteers.